DETERMINAN KEANDALAN PELAPORAN KEUANGAN PEMERINTAH PADA SKPD KABUPATEN KULONPROGO - Purnama Sari, Ratna (Accounting Global Journal, 2019)
The aim of this research is to know determinants of reliability of governmental financial reporting such as human resources quality, information technology utilization and internal control system. This research was done in Satuan Kerja Perangkat Daerah (SKPD) Kulon Progo. The data obtained by questionnaires distributed to 123 respondents consisting of the head and staff of the finance / Accounting department. The data analysis method was multiple linear regression. The result shows that the human resource quality is significantly affected to the reliability of Government Financial Reporting, while information technology utilization and internal control system are not affected. Keywords: human resources quality, information technology utilization, internal control system, reliability of Government Financial Reporting